Preference of Chinese pre-service music teachers and schoolteachers for three culturally diverse musical pieces - Cui, Cancan; Liu, Jin; Zhu, Yun (Frontiers in Psychology, 2024)
Using three musical pieces as musical stimuli from Romania, Brazil, and Saudi Arabia, this study extended Fung's (2007) study by examining Chinese preservice music teachers' (n=115) and schoolteachers' (n=131) personal preferences and external preferences for orchestral, folk, and popular music pieces. Two groups of participants were asked to select their preferred music from three pieces and to provide verbal descriptions of the reasons for their selections. The results showed (a) no significant differences in personal preference between the two groups but statistical significances in external preferences between the two groups; (b) the highest preference rating by both groups of teachers was folk music and the highest forced-choice preference was popular music; (c) statistically significant correlations between personal preference and external preference were evident in both groups across all three pieces; and (d) frequent descriptions by both groups of participants of the pieces in terms of musical characteristics were shared. The implications of this study are as follows. (1) Psychologists and music researchers gain insights about Chinese young adults' listening preferences, which might offer implications for future research in the field of psychology; and (2) By enhancing Deleted: The research questions were as follows: (1) What are the differences in five variables (familiarity, perceived subjective value of music, external preference for musicians, external preference for K-12, and personal preference) between the two groups across the three musical pieces? ( 2) To what extent does preference rating relate to forced-choice preference? (3) To what extent are preservice music teachers' and schoolteachers' personal preferences related to familiarity, the subjective perceived value of the music, and external preference for musicians and K-12 students? (4) When asked directly, what are preservice music teachers' and schoolteachers' verbal descriptions of the pieces? (5) When asked directly, what are the perceived reasons for preservice music teachers' and schoolteachers preferring a piece the most and the least? (6) What is the relationship between preservice music teachers' and schoolteachers' verbal descriptions and the reasons for their preferences? … 2 multicultural awareness, music education teachers and researchers should combine different music styles to broaden students' music horizons.